Upregulation of long non-coding RNA MEG3 in type 2 diabetes mellitus complicated with vascular disease: a case–control study - Chang, Wei-wei; Zhang, Liu; Yao, Xin-ming; Chen, Yan; Zhu, Li-jun; Fang, Zheng-mei; Zhao, Ying; Yao, Ying-shui; Jin, Yue-long (Molecular and cellular biochemistry, 2020)
Previous studies have indicated that long non-coding RNAs (lncRNAs) were closely related to diabetes. In this study, we aimed to explore the possible role and mechanism of lncRNA MEG3 in the occurrence and development of type 2 diabetes mellitus (T2DM) and its vascular complications. A case–control study involving 115 subjects was conducted, including 53 T2DM patients (37 patients with vascular complication and 16 patients without vascular complications) and 62 healthy subjects. We performed real-time polymerase chain reaction (RT-PCR) analysis of the lncRNA MEG3 and miR-146a levels in peripheral blood mononuclear cells (PBMCs) in the 115 samples. We found that the expression of lncRNA MEG3 was upregulated in the T2DM patients with vascular complication (DC group) compared with T2DM patients without vascular complication (D group) ( P < 0.05) and the control group ( P < 0.01). miR-146a levels in DC group were significantly lower compared with control group. There was a significant positive correlation between the expression of lncRNA MEG3 and glucose (GLU) ( r = 0.301, P = 0.0011) and hemoglobin A1C (HbA1c) ( r = 0.477, P = 0.0006). Our study suggests MEG3 may play as an important role in progression of diabetes-related vascular complications, contributing to a novel understanding of pathogenesis and prognosis for diabetes and its complications.